Tirzepatide’s innovative applications in the management of type 2 diabetes and its future prospects in cardiovascular health - Yang, Jingqi; Gu, Yuncheng; Chen, Huaigang; Wang, Hong; Hong, Lang; Li, Bin; Yang, Liu (Frontiers in Pharmacology, 2024)
Tirzepatide, a novel GLP-1/GIP dual receptor agonist, shows significant advantages in glycemic management and weight control. By summarizing the results of the SURMOUNT and SURPASS clinical trials, we evaluate the efficacy and safety of tirzepatide in reducing blood glucose and weight. These trials indicate that tirzepatide significantly lowers HbA1c levels (with a maximum reduction of 2.24%) and promotes weight loss (up to 11.2 kg) with good tolerability. However, there are still some challenges in its clinical application, including high treatment costs and gastrointestinal discomfort. Additionally, the safety and efficacy of tirzepatide in special populations, such as patients with renal impairment, require further investigation. Future large-scale clinical trials, such as SURPASS-CVOT and SUMMIT, are expected to further verify the long-term benefits of tirzepatide in cardiovascular health management, providing stronger evidence for its comprehensive treatment of diabetes and its complications